Adaptaciones curriculares en trastorno de déficit de atención e hiperactividad en estudiantes de segundo grado de la Unidad Educativa Mario Paltin Lavanda, 2023-2024 - Nole Medina, Miriam Johanna (2024)
Nowadays, the inclusive education system has enabled children with different disorders to have access to regular education, and that is why the government, in order to guarantee a quality and welcoming education, has implemented curricular adaptations in the general curriculum, which are flexible and individually designed according to each student needs. In this study, they are adapted to students with Attention Deficit Hyperactivity Disorder (ADHD). The main objective of this paper was to analyse the curricular adaptations to Attention Deficit and Hyperactivity Disorder. We selected as our study population the students from the second grade of the Unidad Educativa Mario Paltin Lavanda, 2023- 2024, resulting in a total of 1 teacher and 6 students. This research was of a qualitative approach and a descriptive type, with a non-experimental design and transversal axis, it also implemented the analytical, inductive and scientific methods: We used the interview and observation techniques. The results evidenced that the students present the most common characteristics of ADHD, it was also possible to perceive the teacher doesn’t have the necessary knowledge of new tools that can be included in the curricular adaptations, which will make it possible for her to improve the teaching-learning process. Consequently, we reached the conclusion that students with Attention Deficit Hyperactivity Disorder (ADHD) have the most common characteristics, which include hyperactivity, attention difficulties, impulsivity and low academic performance, for which a pedagogical proposal called "Awareness-raising instructions for teachers of students with ADHD" was risen, it aims to provide teachers with updated information and relevant technological tools.